1995
DOI: 10.2165/00003088-199528020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Rifabutin

Abstract: The clinical effectiveness of rifabutin for prophylaxis of disseminated Mycobacterium avium complex infection has recently been demonstrated in HIV-positive patients with low CD4 counts. Rifabutin is a newly marketed, semisynthetic antimycobacterial agent similar to rifampicin (rifampin) in structure and activity. However, rifabutin has important pharmacokinetic differences compared with rifampicin. Rifabutin has relatively low oral bioavailability; about 20% after single dose administration. With long term ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 53 publications
1
50
0
Order By: Relevance
“…Rifabutin has an apparent terminal half-life of 45 h (range, 16 to 69 h) (32). Due to the potent CYP induction liability of rifampin, rifabutin is used as an alternative to rifampin in individuals infected with HIV who are coinfected with Mycobacterium tuberculosis (3).…”
mentioning
confidence: 99%
“…Rifabutin has an apparent terminal half-life of 45 h (range, 16 to 69 h) (32). Due to the potent CYP induction liability of rifampin, rifabutin is used as an alternative to rifampin in individuals infected with HIV who are coinfected with Mycobacterium tuberculosis (3).…”
mentioning
confidence: 99%
“…Co-administration of rifabutin with ritonavir, as is common in patients with HIV disease, increases the Area Under the Concentration-time curve (AUC) of Rifabutin by 35 times, compared with administration of rifabutin alone [5,6]. This increases the propensity for rifabutin to exert its ocular idiosyncratic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of symptoms can occur as early as 2 weeks to 7 months following initiation of therapy [4]. It can be seen with doses that range from as low as 300mg a day to 1800mg a day [4], although side effects are less common in the standard prophylactic dose of 300mg [5,6]. It is usually under diagnosed, and the patient is subjected to various laboratory tests to establish an etiology for the uveitis.…”
mentioning
confidence: 99%
“…The dose range of rifabutin associated with uveitis goes between 300 and 1800 mg daily [5,9]. Shafran and colleagues demonstrated that patients on 300 mg/day of rifabutin rarely developed uveitis, and when it occurred, it took at least 7 months of medication use for the uveitis to develop [3].…”
Section: Discussionmentioning
confidence: 99%
“…Shafran and colleagues demonstrated that patients on 300 mg/day of rifabutin rarely developed uveitis, and when it occurred, it took at least 7 months of medication use for the uveitis to develop [3]. Skinner and Blaschke later confirmed that drug related uveitis was unusual at the recommended dose of 300 mg/day [9]. Our patient was on 150 mg daily of rifabutin for 4 months before he developed uveitis but he was also taking ritonavir 100 mg/d and fluconazole 200 mg/week.…”
Section: Discussionmentioning
confidence: 99%